Adoption of unmanned aerial vehicles for pesticide application: Role of social network, resource endowment, and perceptions. (February 2021) - Wachenheim, Cheryl; Fan, Linfeng; Zheng, Shi
Abstract: Unmanned aerial vehicle technology is a promising alternative for sustainable agriculture production to more traditional technologies used in China. This paper considers factors affecting adoption of unmanned aerial vehicles for spraying pesticides among farmers in Jilin Province, China. Gender (male), percentage of income from agriculture, cultivated land area, within-family village leadership, number of borrowing channels, and positive attitudes towards the technology had a positive effect on adoption intention. Positive attitude toward traditional technology and higher income had a negative effect. Policy recommendations include continued work in improving access to rural financing, facilitating early adopters, and technology promotion. Highlights: Increased borrowing options increase willingness to adopt unmanned aerial vehicles for pesticide application. A relationship with village cadre increases willingness to adopt unmanned aerial vehicles for pesticide application. Positive perceptions about usefulness of unmanned aerial vehicle technology increases willingness to adopt.